PENGARUH PEMASARAN DIGITAL TERHADAP VOLUME PENJUALAN RUBEKA CAFÉ - Louis Alexandro, Vincent; Rosie Oktavia Puspita Rini (JURNAL MANAJEMEN KULINER, 2024)
Every business has ways to increase sales, sales targets and achieve company goals through digital marketing strategies. This research aims to determine the influence of digital marketing on the sales volume of Rubeka café Batam. The method in this research was quantitative descriptive by distributing questionnaires to 323 respondents. Data collection used in this research was observation, documentation, interviews and questionnaires. The sample from the population in the study was consumers of Rubeka Café Batam. With a total of 323 samples, the sampling technique used was simple random sampling. The results of this research data analysis using SPSS version 19. And the results of the coefficient of determination (R2) from the influence of the digital marketing variable (X) can explain variations in sales volume (Y) of 68.4%. And 31.6% of the variation in variables is not in this study. It can be concluded that in this research the digital marketing variable has a positive influence and significant data has a positive value on the sales volume (Y) of Rubeka Café Batam.